Involving Children with Special Needs in Managing a Digital-based Waste Bank - Febrita Ardianingsih; Asri Wijiastuti; Siti Masitoh (International Inclusion Development and Cooperation, 2022)
The Covid-19 pandemic has increased plastic waste. Those may cause microplastics and nanoplastics contaminants in soil, water, and air that have the potential to interfere with environmental health and human health. Waste management from the source is important in solving the problem of plastic waste, one of which is through a waste bank. Can children with special needs be involved in managing a digital-based waste bank? This study aims to determine: (1) the skills of children with intellectual disabilities in sorting waste, and (2) the skills of children with hearing impairments to record waste transactions digitally. This research is a one-group posttest only design. The sample was carried out purposively, totaling 10 children with intellectual disabilities and 14 children with hearing impairment in special high schools. Data were collected through tests after training. Data analysis used descriptive statistics. The research findings show that: (1) children with intellectual disabilities have very good skills to sort waste with an average score of 84.40, and (2) children with hearing impairment have good skills to record waste transactions digitally with an average score of 80.36. It indicates that children with intellectual disability and hearing impairment have the potential to be involved in digital-based waste management. This involvement may develop an awareness of children with special needs in environmental health.